Mechanics of curved composites (piecewise-homogeneous body model) - Akbarov, SD; Guz, AN (CONSULTANTS BUREAU, 2002)
A review is made of studies on the mechanics of curved composites carried out using the piecewise-homogeneous body model and the exact three-dimensional equations of the theory of elasticity and viscoelasticity. Relevant problem formulations and solution methods are considered and some typical results on the influence of structural distortion on the mechanical behavior of composites are analyzed. Subjects for near-term studies are proposed.
Keywords: 3-DIMENSIONAL THEORY; DEFORMABLE-BODIES; STRESS STATE; STABILITY; CRACK; PLATE; COMPRESSION; FRACTURE; ELEMENTS; LAYERS; Mechanics